Use of remote sensing data for long-term monitoring of agricultural landscapes - Sergey Anatolevich Antonov; Andrey Vladimirovich Skripchinskii (Наука. Инновации. Технологии)
The article presents an analysis of the joint use of data from the Landsat 8 and Sentinel 2 satellites to form long-term monitoring of agricultural landscape vegetation using example of the Georgievsky district in Stavropol Region. The features of the satellite data correction to assess the state of vegetation are considered. The statistical analysis of the vegetation index (NDVI) obtained from the data of Landsat 8 and Sentinel 2 satellites revealed the identity of statistical indicators. The possibility of long-term satellite monitoring of vegetation health from Landsat 8 and Sentinel 2A satellites by calculating the vegetation index (NDVI) is established and statically proven on the basis of images with geometric and radiometric correction.